The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Psychiatrie, genre et sexualités dans la seconde moitié du XXe siècle - Arena, Francesca; Chiletti, Silvia; Coffin, Jean-Christophe (Comment s'en sortir?, 2015)
Les diagnostics cliniques et les différentes nosographies psychiatriques qui ont été établies dans la deuxième moitié du XXe siècle, notamment dans les différentes éditions du manuel américain de diagnostic et statistique des troubles mentaux (DSM), montrent qu'un nombre très significatif de troubles sont envisagés comme étant genrés. Plusieurs controverses ont marqué l'histoire de ces diagnostics depuis les années 1950 : d'abord celui des sexualités et de leurs frontières floues, ensuite la notion controversée d'identité de genre, enfin la problématique des troubles périnataux. Si le principe de différentiation constitue un élément incontournable de la pensée psychiatrique, le façonnage et l'usage du concept de « genre » révèlent des tensions entre la psychiatrie et la société (notamment les mouvements gay, féministes et trans) mais aussi au sein de la psychiatrie elle-même. Il apparaît évidant que, dans les classifications psychiatriques, les normes sociales de genre sont intégrées de manière passive et acritique, au point que l'usage du concept de genre peut amener à l'inverse à renforcer la naturalisation des comportements alors même que, dans les sciences sociales, il est utilisée pour interroger et déconstruire la prétendue naturalité de la différence des sexes.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques; violences; états-unis

Redéfinir l’endométriose : De la critique féministe à la santé environnementale - Čapek, Stella M. (Sur la piste environnementale : Menaces sanitaires et mobilisations profanes, 2013)
Code: Sur la piste environnementale : Menaces sanitaires et mobilisations profanes
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; inégalités; justice reproductive; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; écoféminisme; états-unis

Contested psychiatric ontology and feminist critique: ‘Female Sexual Dysfunction’ and the Diagnostic and Statistical Manual - Angel, Katherine (History of the Human Sciences, 2012)
In this article I discuss the emergence of Female Sexual Dysfunction (FSD) within American psychiatry and beyond in the postwar period, setting out what I believe to be important and suggestive questions neglected in existing scholarship. Tracing the nomenclature within successive editions of the American Psychiatric Association’s Diagnostic and Statistical Manual (DSM), I consider the reification of the term ‘FSD’, and the activism and scholarship that the rise of the category has occasioned. I suggest that analysis of FSD benefits from scrutiny of a wider range of sources (especially since the popular and scientific cross-pollinate). I explore the multiplicity of FSD that emerges when one examines this wider range, but I also underscore a reinscribing of anxieties about psychogenic aetiologies. I then argue that what makes the FSD case additionally interesting, over and above other conditions with a contested status, is the historically complex relationship between psychiatry and feminism that is at work in contemporary debates. I suggest that existing literature on FSD has not yet posed some of the most important and salient questions at stake in writing about women’s sexual problems in this period, and can only do this when the relationship between ‘second-wave’ feminism, ‘post-feminism’, psychiatry and psychoanalysis becomes part of the terrain to be analysed, rather than the medium through which analysis is conducted.
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; europe; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

La violence exercée contre les jeunes filles autochtones : le problème, sa face cachée, les sources d’espoir et les interventions possibles - Down, Pamela J. (Violences faites aux femmes, 2008)
Section: xxiii, 504 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; autochtones; canada; cours; disparitions des filles et des femmes autochtones; périodes historiques; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; trs3500; violences; violences envers les femmes*; violences sexistes et sexuelles

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Le discours des défenseurs des droits des hommes sur la violence conjugale: Une analyse critique - Brodeur, Normand (Service social, 2003)
Se disant victimes d'injustices non reconnues, les défenseurs des droits des hommes dénoncent le discours féministe sur la violence masculine et les politiques sociales mises en place depuis vingt ans pour combattre la violence conjugale. Cet article résume leurs principaux arguments à partir d'une analyse de contenu de trois ouvrages publiés au Québec. La seconde partie de l'article situe ces arguments à l'intérieur des controverses autour de la définition de la violence, de la violence des femmes et du maintien d'un équilibre entre les droits des victimes et ceux des personnes accusées devant les tribunaux. Elle fait aussi état de données qui remettent en question les thèses des défenseurs des droits des hommes sur la symétrie générale de la violence entre les sexes et sur la discrimination systématique dont les hommes seraient victimes au sein du système judiciaire.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; antiféminisme; approches et analyses; canada; couple; cours; discipline; premier cycle; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; trs1205; violences

La scission politique du féminisme international sur la question du “ trafic des femmes ” vers la “ migration ” d’un certain féminisme radical ? - Toupin, Louise (Recherches féministes, 2003)
Cet article donne un aperçu de l’argumentation qui met en lumière et différencie les principales coalitions internationales féministes luttant contre ce qui est couramment appelé le « trafic des femmes ». L’argumentation mise en évidence ne touche que la définition du phénomène et le différend qui sépare les coalitions sur le sujet, ainsi que leurs stratégies respectives pour l’éradiquer. L’auteure souligne en conclusion certains tangentes du féminisme radical qui, à son avis, se voient désormais remises en cause à l’occasion du débat sur les migrations des femmes. Ce débat entraînera-t-il, à son tour, se demande-t-elle, la migration d’un certain féminisme radical ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; histoire du féminisme; histoire et politique; intersectionnalité; miitance; patriarcat; premier cycle; prostitution; périodes historiques; ressource en ligne; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; traite des femmes; travail; travail du sexe; violences

Femmes, violences et espace public: une réflexion sur les politiques de sécurité - Lieber, Marylène (Lien social et Politiques, 2002)
Lorsqu'on se penche sur les politiques publiques concernant les violences en France, on relève une division des compétences entre les politiques dites « de sécurité » et les politiques « contre les violences faites aux femmes ». On constate que les politiques de sécurité, en se basant sur les statistiques de criminalité et de victimation, portent essentiellement sur l'espace public et marginalisent les violences faites aux femmes dans l'espace privé. Pour autant, elles ne prennent pas non plus en considération les violences perpétrées à leur encontre dans l'espace public. Or, divers exemples venant de pays étrangers esquissent des réponses faites par les pouvoirs publics à ces violences
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; pol4102; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; sécurité; thématiques; violences

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres